Investigation on anti-proliferation properties of porcupine bezoar (hystrix brachyuran) extracts exposed on hela cells lines combined with electroporation technique - Azizulkarim, Azra Hazwanie; Abdul Jamil, Muhammad Mahadi; Adon, Mohamad Nazib; Abdul Wahab, Ridhwan; Tengku Ibrahim, Tengku Nadzlin (Universiti Teknikal Malaysia Melaka, 2018)
Electroporation (EP) is a technique whereby the biophysical changes on the cells that induced external high-intensity electrical field pulses in order to enhance applications in the medical field. It is a molecular biology technique in order to create pores through a cell wall membrane, boost the permeability of the cell membrane, and support chemicals, drugs or DNA to be imported into Hela cells. While by combining electroporation (EP) technique with porcupine bezoar (PB) extract might reduce the proliferation of HeLa cells because this compound extract has the ability of anti-proliferation and also anti-angiogenesis properties for controlling cancer cell growth. This research concentrate on reviewing and analyses the basic concepts and methods of combining electroporation and porcupine bezoar (PB) extract as applied in cancer treatment application. The combination of this technique might be a new alternative for anti-cancer treatment. The combination of this technique might be a new way for anti-cancer treatment. © 2018 Universiti Teknikal Malaysia Melaka. All rights reserved.